Naravni materiali za izdelavo sodobnih lepil za les - Ugovšek, Aleš (Les (Ljubljana), 2010)
Abundant amounts of plants and their products can be found in the nature. They can be used as potential material to produce wood adhesives because of their ability to bond different materials. Furthermore, their environmental pollution is minimal, volatile organic compound emission is low, they are renewable and affordable in their basic form. Production of wood adhesives based on plants and their products is a sphere where many studies and attempts of industrial applications have already been done. Results of these studies and efforts to develop wood adhesives based on soy, carbohydrates fro mnatural sources and other plant materials are presented in this article.
Keywords: lepila; kavčuk; ogljikovodiki; proteini